The Association Between Early Age-Related Hearing Loss and Brain Beta-Amyloid - Golub, Justin S. (Laryngoscope, 2020)
OBJECTIVE: To analyze the association between early audiometric age-related hearing loss (HL) and brain beta-amyloid, the pathologic hallmark of Alzheimer’s disease (AD) METHODS: Cross-sectional analysis of 98 participants in a cohort study of hearing and brain biomarkers of AD. The primary outcome was whole brain beta-amyloid standardized uptake value ratio (SUVR) on positron emission tomography. The exposure was hearing, as measured by either pure tone average or word recognition score in the better ear. Covariates included age, gender, education, cardiovascular disease, and hearing aid use. Linear regression was performed to analyze the association between beta-amyloid and hearing, adjusting for potentially confounding covariates. RESULTS: Mean age was 64.6 ± 3.5 (SD) years. In multivariable regression, adjusting for demographics, education, cardiovascular disease, and hearing aid use, whole brain beta-amyloid SUVR increased by 0.029 (95% CI = 0.003, 0.056) for every 10 dB increase in pure tone average (P=0.030). Similarly, whole brain beta-amyloid SUVR increased by 0.061 (0.009, 0.112) for every 10% increase in word recognition score (P=0.012). CONCLUSION: Worsening hearing was associated with higher beta-amyloid-burden, a pathologic hallmark of AD, measured in vivo with PET scans.